2021
DOI: 10.1016/s0140-6736(21)01429-x
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety of an inactivated whole-virion SARS-CoV-2 vaccine (CoronaVac): interim results of a double-blind, randomised, placebo-controlled, phase 3 trial in Turkey

Abstract: Background CoronaVac, an inactivated whole-virion SARS-CoV-2 vaccine, has been shown to be well tolerated with a good safety profile in individuals aged 18 years and older in phase 1/2 trials, and provided a good humoral response against SARS-CoV-2. We present the interim efficacy and safety results of a phase 3 clinical trial of CoronaVac in Turkey.Methods This was a double-blind, randomised, placebo-controlled phase 3 trial. Volunteers aged 18-59 years with no history of COVID-19 and with negative PCR and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

46
691
6
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 803 publications
(762 citation statements)
references
References 28 publications
46
691
6
19
Order By: Relevance
“…A key evidence gap, as raised in the WHO EUL for CoronaVac,11 has been the effectiveness of this vaccine in the elderly population, because this age group was not well represented in Brazilian and Turkish randomised controlled trials 571011. We found that two doses of CoronaVac administered at an average interval of four weeks had an overall effectiveness against symptomatic covid-19 of 47% (39% to 54%) in a population with a mean age of 76 years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A key evidence gap, as raised in the WHO EUL for CoronaVac,11 has been the effectiveness of this vaccine in the elderly population, because this age group was not well represented in Brazilian and Turkish randomised controlled trials 571011. We found that two doses of CoronaVac administered at an average interval of four weeks had an overall effectiveness against symptomatic covid-19 of 47% (39% to 54%) in a population with a mean age of 76 years.…”
Section: Discussionmentioning
confidence: 99%
“…A preliminary aggregated analysis using weekly times series of covid-19 deaths in Brazil found a relative decrease in mortality among those aged ≥70 years compared with all ages after vaccination with CoronaVac and ChAdOx1 nCov-19,45 suggesting a discernible impact of vaccination on mortality at the population level. Additional investigation is required to determine the duration of protection conferred by CoronaVac 71923…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-introduction vaccine studies provide practitioners and policy makers with the kind of evidence that clinical trials cannot—including real world vaccine effectiveness against multiple clinical outcomes. Two linked studies12 that together examined three covid-19 vaccines, add to mounting evidence that efficacy reported in clinical trials translates well to the real world 34567. The studied vaccines—CoronaVac (Sinovac Biotech), BNT162b2 (Pfizer-BioNTech), and mRNA-1273 (Moderna)—performed well in preventing severe covid-19 and deaths in adults after two doses; a single dose was significantly less effective, and all three vaccines were effective (although demonstrably less so) against milder disease.…”
mentioning
confidence: 99%